Conjugation of gold nanoparticles with multidentate surfactants for enhanced stability and biological properties. Issue 1 (14th November 2022) - Rotem, Rany; Giustra, Marco; Arrigoni, Federica; Bertolini, Jessica A.; Garbujo, Stefania; Rizzuto, Maria A.; Salvioni, Lucia; Barbieri, Linda; Bertini, Luca; De Gioia, Luca; Colombo, Miriam; Prosperi, Davide
Abstract : Removal of polymer excess in NPs suspension causing colloidal instability. Multidentate polymer is a solution to avoid this critical phenomenon in the application of nanotechnology. Abstract : This work originated from the need to functionalize surfactant-coated inorganic nanoparticles for biomedical applications, a process that is limited by excess unbound surfactant. These limitations are connected to the bioconjugation of targeting molecules that are often in equilibrium between the free aliquot in solution and that which binds the surface of the nanoparticles. The excess in solution can play a role in the biocompatability in vitro and in vivo of the final nanoparticles stock. For this purpose, we tested the ability of common surfactants – monothiolated polyethylene glycol and amphiphilic polymers – to colloidally stabilize nanoparticles as excess surfactant is removed and compared them to newly appearing multidentate surfactants endowed with high avidity for inorganic nanoparticles. Our results showed that monothiolated polyethylene glycol or amphiphilic polymers have an insufficient affinity to the nanoparticles and as the excess surfactant is removed the colloidal stability is lost, while multidentate high-avidity surfactants excel in the same regard, possibly allowing improvement in an array of nanoparticle applications, especially in those stated.